Degumming of sunflower oil with degumming agents based on flour - Demydova, A. O.; Aksonova, O. F.; Piven, O. M. (Харківський державний університет харчування та торгівлі, 2020)
One of the main directions of development of the food industry is to increase the safety and quality of products, the development of new technologies that use soft treatment regimes with the rejection of the use of additional chemicals. The article proves the effectiveness of degumming of sunflower oil when using aqueous suspensions of wheat and pea flour: degumming in the presence of 0.1% wheat flour and 0.06% citric acid reduces the phospholipid content in refining oil to 0.04% in terms of stearooleolecitin (when using 0.1% pea flour and 0.06% citric acid –up to 0.045%, respectively). The efficiency of degumming when using starch solutions is much lower: under the same conditions of degumming (0.1% starch and 0.06% citric acid), the final phospholipid content in refining oil is 0.075%. Degumming agent based on polyvinyl alcohol was the most effective (phospholipid content in refining oil – 0.039%), but due to its synthetic nature, we consider more promising to use moisturizing agents based on flour. The obtained refining oils meet all the main quality indicators, and such indicators as phospholipid content, acid value, peroxide value, color are significantly lower compared to the results of traditional degumming (aqueous or acidic). Also, degumming cleansing with wheat or pea flour can be recommended for oils of low quality, with the alignment of quality indicators to values that meet the requirements of regulatory documents. Equalization of oil quality due to the adsorption effect of flour looks like a promising approach due to safety and low cost. The possibility of delamination of the wet gum with the separation of 40% of the aqueous phase by heating it to 70 °C in the presence of 5% sodium chloride was investigated. It is proposed to use the obtained wet gum with high protein content without drying. Such a phospholipid product will be characterized by a higher biological value as a result of the absence of destructive thermal exposure.

Доведено ефективність гідратування соняшникової олії за умови використання водних суспензій борошна пшеничного та горохового. Гідратування за наявності 0,1% пшеничного борошна та 0,06% лимонної кислоти приводить до зменшення вмісту фосфоровмісних речовин у гідратованій олії до 0,04% у перерахунку на стеаролеолецитин. Досліджено можливість розшарування фосфоліпідної емульсії в разі застосування деемульгатора (хлористого натрію).
Гідратування соняшникової олії з гідратуючими агентами на основі борошна
Keywords: degumming; phospholipids; sunflower oil; flour; wet gum; sodium chloride; гідратування; фосфоліпіди; соняшникова олія; фосфоліпідна емульсія; хлорид натрію